Undergraduates' Electronic Resources Diffusion at the Peking University: An Exploration on Language Impacts. Issue 3 (2nd April 2017) - Zhou, Qingshan; Li, Zhiqiang; Huang, Xifei; Chiu, Dickson K. W.
Abstract : Most studies on Chinese academic resource selection have used a qualitative approach, focusing on issues such as resource distribution and accessibility. To fill the research gap, the current article analyses the responses of 190 undergraduate students of the Peking University to a questionnaire survey, revealing various academic resources' access methods, usage frequency, and access obstacles, while exploring underlying factors affecting resource usage with a focus on the language impacts. Further, the application of the innovation diffusion model to study the utilization of library electronic resources is novel. The current findings showed that open-shelf books, electronic journals, and open-access resources were highly utilized because of their high quality. Electronic resources were displacing printed resources. Based on Bass's innovation diffusion model, diffusion of different electronic resources among undergraduate students fit well with the S-curve, though with significantly different slopes, for example, there was a significantly different diffusion rate between English and Chinese resources. In particular, difficulties in accessing Western databases was identified because of students' limited information literacy and language ability.